Forecaster - Coasters Association (2008)

CHSSN Telehealth Program & Follow-up Intervention Project : 2007-2008 - Community Health and Social Services Network (CHSSN); McGill University Health Centre (2008)
The Community Health Education Program (CHEP) is a dynamic program that facilitates distance community learning of health and social information for English-speaking Quebecers in remote communities, via five different components: videoconferencing, telephone conferencing, videoconferencing Session DVD’s, community radio (Internet access), follow-up activities (face-to-face)

CHSSN Community Radio Project 2007-2008 - Community Health and Social Services Network (CHSSN) (Community Health and Social Services Network (CHSSN), 2008)
In winter 2007, the CHSSN carried out a pilot project in conjunction with Townshippers’ Association to disseminate community health information via community radio to test the efficacy of using this medium to extend the outreach of the Network Partnership Initiative (NPI). Two call-in shows -- Dependencies and Mental Health -- were broadcast by CJMQ-FM in Lennoxville, and an edited recording of the show on Dependencies was re-broadcast on CJAS in St-Augustin. Based on the success of the 2007 pilot, for winter 2008 the community radio project was expanded to include more regions, a wider range of informational programming and Internet dissemination.
Keywords: Official Language Minority Community (OLMC)

The Baseline Data Report 2007-2008 : Quebec's Social and Health Survey Information - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2008)
The Health and Social Services Networking and Partnership Initiative (HSSNPI) is a funding program of the Quebec Community Groups Network mandated by Health Canada as a measure of the Federal Action Plan for Official Language Communities. The HSSNPI aims to support the creation of durable links and joint action between English-speaking communities and Quebec’s health and social services system. The Baseline Data Report is a series produced by the Community Health and Social Services Network (CHSSN) to serve as a relevant and comprehensive knowledge base regarding the health status and vitality of Quebec’s English‐speaking population. The report is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders to develop strategies to improve the well‐being of their constituencies.
Keywords: Official Language Minority Community (OLMC)

Community NetLink - Community Health and Social Services Network (CHSSN) (2008)